2021
DOI: 10.1371/journal.pone.0247296
|View full text |Cite
|
Sign up to set email alerts
|

Social factors associated with reversing frailty progression in community-dwelling late-stage elderly people: An observational study

Abstract: Frailty is considered to be a complex concept based mainly on physical vulnerability, but also vulnerabilities in mental/psychological and social aspects. Frailty can be reversible with appropriate intervention; however, factors that are important in recovering from frailty have not been clarified. The aim of the present study was to identify factors that help an individual reverse frailty progression and characteristics of individuals that have recovered from frailty. Community-dwelling people aged ≥75 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 27 publications
7
50
1
Order By: Relevance
“…Because frailty could be reversible with appropriate intervention, 2 early diagnosis and intervention approaches are crucial. However, the diagnosis of frailty lacks definite criteria.…”
Section: Introductionmentioning
confidence: 99%
“…Because frailty could be reversible with appropriate intervention, 2 early diagnosis and intervention approaches are crucial. However, the diagnosis of frailty lacks definite criteria.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, the relationship between social participation and each factor in older adults has been investigated. In addition, in previous studies, social participation was associated with better cognitive function [19][20][21][22][23] ; less depressive symptoms [24][25][26][27][28] and psychological distress 29 ) ; more instrumental activities of daily living [30][31][32] ; less functional disability [33][34][35][36][37][38] ; better physical activity [39][40][41] ; better life-space mobility 42 ) ; better mental health 43 ) ; self-related health 44 ) and health-related quality of life 45 ) ; social isolation 46,47 ) ; medical care costs 46,47 ) ; and a lower incidence of dementia 48) , frailty [49][50][51] , and mortality 52) in Japanese older adults (Fig. 1).…”
Section: Fifth Levelmentioning
confidence: 85%
“…Of the 42,775 community-dwelling older adults from 16 studies (mean follow-up duration: 3.9 years), the condition of 23.1% of individuals with pre-frailty improved to the robust state, compared to only 3.3% of those who were in the state of frailty at baseline [ 19 ]. A recent study found that participation in exercise-based social activities is associated with the reversal of frailty progression; however, the two-stage improvement from frailty to robustness was observed in only 5.8% of the population [ 20 ]. This suggests that it is important to maintain the prefrailty state for a long time and to prevent the deterioration of the frail state.…”
Section: Discussionmentioning
confidence: 99%